Evaluation of the Effectiveness of Pulsed Ultraviolet Devices in Medical Premises of the Emergency Department of a Hospital Under Conditions of Intensive Patient Flow - B. L. Kurilin; N. E. Drozdova; A. Yu. Perminov; E. V. Kislukhina; Ya. V. Kulikova; N. S. Fomenko; A. V. Shapoval; V. I. Drozdova; A. R. Samarin (Неотложная медицинская помощь, 2025)
INTRODUCTION. In the State Budgetary Healthcare Institution N.V. Sklifosovsky Research Institute for Emergency Medicine of the Moscow Health Department (hereinafter referred to as the Institute), the number of visits to the admission and diagnostic departments has more than doubled over the past 15 years. Emergency patients are considered potentially infected, therefore, it is necessary to carry out high-quality and timely disinfection of open surfaces and air. The use of pulsed ultraviolet disinfection technologies is effective and cost-effective.AIM OF THE STUDY. Evaluation of the microbiological efficiency and economic feasibility of using a portable pulsed ultraviolet unit for disinfecting air and open surfaces during emergency patient reception in conditions of intensive patient flow for the purpose of preventing healthcare-associated infections.MATERIAL AND METHODS. To disinfect the air and surfaces of the premises, we used the “Alpha-09 portable pulse ultraviolet unit” (hereinafter referred to as the Unit) manufactured by NPP Melitta LLC, Russia.To conduct the study, three rooms were designated in the admissions department: two experimental rooms and one control room.Routine wet cleaning of the premises was carried out twice a day, and also as needed. Preventive disinfection of work surfaces was carried out after each patient by wiping with the use of approved products.The experimental premises were treated according to a single standard algorithm, including treatment with the Installation.To collect microbiological swabs, sampling points were defined in the studied premises (4 in each). The sampling frequency was three times a week, twice a day. A surface swab collection table was filled in for each of the premises. Surface swab samples were signed accordingly and transferred to the bacteriological laboratory for testing. Surface swabs were collected in accordance with MUK 4.2.2942-11. The species affiliation of microorganisms was confirmed by MALDI-TOF-MS.The obtained results were processed by standard means of mathematical statistics using R, a free software computing environment. The reliability of differences in numerical values was determined using Student’s t-test, and categorical values were determined using the χ2-test or McNamara test .To assess the economic efficiency of using pulsed UV devices, methods of economic analysis and investment assessment were used.RESULTS. 1. An additional 3-fold irradiation of the procedure room with a pulsed ultraviolet installation during an 8-hour shift reduced the number of positive surface swab samples 12-fold; 2-fold irradiation – 5-fold, compared to the standard procedure for processing rooms.2. Comparison of annual comparable costs of pulsed ultraviolet devices with annual effects from their use showed the economic feasibility of their use.CONCLUSION. The use of short-term pulsed UV irradiation for disinfection of premises between patient visits is epidemiologically effective and economically feasible.